Analysis of Tripleband Single Layer Proximity Fed 2x2 Microstrip Patch Array Antenna - Abraham, Jacob; Suriyan, Kannadhasan (International Journal of Electrical and Computer Engineering Systems, 2022)
Microstrip patch antennas that are multiband and downsized are required to suit the high demand of modern wireless applications. To meet this need, a one-of-a-kind triple band array antenna has been proposed. The proposed 2x2 microstrip patch array, which comprises of four hexagon-shaped radiating patches are electromagnetically excited by a centrally positioned microstrip feed line in the same plane along with a slotted ground plane, is investigated. CST Microwave Studio, a powerful 3D electromagnetic analysis programme, was used to design and optimize the array antennas. The 2x2 array antenna was constructed on a FR-4 substrate with a dielectric constant of 4.3, a loss tangent of 0.001, and a height of 1.6mm. To optimize energy coupling from the feed line to the radiating patches, the ground plane has an H-shaped groove cut into it. The suggested 2x2 array antenna’s multi- frequency behaviour is shown. Three resonant peaks were detected at 1.891GHz, 2.755GHz, and 3.052GHz. The observed bandwidths for these resonances are 234MHz, 69MHz, and 75MHz, respectively, with measured gains of 7.57dBi, 6.73dBi, and 5.76dBi. The goal of this work is to design, build, and test a single layer proximity fed array antenna. Standard proximity fed array antennas contain two substrate layers; however this array antenna has only one. As a consequence, the impedance matching and alignment are better. Simulated and experimental results showed that the this 2x2 array antenna operates in various important commercial bands, such as L and S bands and the array antenna might be beneficial for a wide range of wireless applications. The proposed antenna has good Impedance, S11, and radiation qualities at resonant frequencies. In this work, the 2x2 array antenna with hexagon-shaped radiating patches was successfully created utilizing the single layer proximity fed antenna concept and gap coupled parasitic patches.